EFFECT OF APPLYING SLOW DEEP BREATHING TECHNIQUE WITH YLANG AROMATHERAPY ON LOWERING BLOOD PRESSURE AND ANXIETY LEVELS: PENGARUH PENERAPAN TEKNIK SLOW DEEP BREATHING DENGAN AROMATERAPI KENANGA TERHADAP PENURUNAN TEKANAN DARAH DAN TINGKAT KECEMASAN - Mimik Christiani; Ixora Ixora; Putri Sintya Rahmawati (Jurnal Keperawatan Terapan, 2023)
In stroke sufferers, anxiety can trigger an increase in blood pressure. A slow deep breathing exercise is an action carried out consciously to regulate breathing slowly and deeply to create a relaxing effect. One of the relaxation techniques is giving aromatherapy in the sufferer's environment it can create a comfortable atmosphere and provide a positive influence. The research aimed to determine the effect of applying the slow deep breathing technique with ylang-ylang aromatherapy to reduce blood pressure and anxiety levels in stroke patients in the Stroke Unit of Dr Soedomo Trenggalek Hospital. The design of this research was descriptive and quantitative with experimentation. The research was carried out using the Intact Group Comparison pre-experiment method by dividing the variables into two groups, namely the experimental group and the control group. The statistical test resulted in the slow deep breathing exercise group with ylang-ylang aromatherapy affected reducing systolic and systolic blood pressure with a p-value of 0.000 (<0.05) and the statistical test resulted on the slow deep breathing exercise group showed a change in reducing systolic blood pressure and diastolic with a p-value of 0.000 (<0.05). Based on the result, it was concluded that there were differences in the average reduction in blood pressure and anxiety levels between the exercise intervention groups slow deep breathing with Ylang Ylang aromatherapy and the slow deep breathing exercise intervention group. The use of slow deep breathing using Ylang Ylang aromatherapy was more effective in reducing blood pressure and anxiety levels experienced by patients.